A Look at the Time Series of NDVI and NDWI at a Wildfire Site in California, USA - Indumathi Jeyachandran (Geoid, 2025)
California has experienced some of the deadliest wildfires in the recent years. Thomas Fire is the eighth largest wildfire in the state of California. In this paper, the correlation between vegetation health and canopy water content and wildfire occurrences is analyzed using Thomas Fire site as the case study site. Time series of Landsat 8 OLI and TIRS Level -1 GeoTIFF data during the period of 2013 to was processed in Esri ArcMap 10.7, and Normalized Difference Vegetation Index (NDVI) and Normalized Difference Water Index (NDWI) were computed. The results of the case study demonstrate the potential of Landsat 8 surface reflectance - derived Normalized Difference Vegetation Index (NDVI) and Normalized Difference Water Index (NDWI) to monitor and identify areas susceptible to wildfire triggers and occurrences.